2019
DOI: 10.1089/lrb.2019.0024
|View full text |Cite
|
Sign up to set email alerts
|

LIMPRINT: Estimation of the Prevalence of Lymphoedema/Chronic Oedema in Acute Hospital in In-Patients

Abstract: Background: To estimate the prevalence of lymphedema/chronic edema (CO) and wounds in acute hospital inpatients in five different countries. Methods and Results: A point-prevalence study was carried out during working day periods in six general hospitals in four countries (Denmark, France, United Kingdom, and Australia) and one hospital oncology inpatient unit in one other country (Ireland). The study used validated clinical tools for the assessment and collection of da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 12 publications
(14 reference statements)
2
14
0
Order By: Relevance
“…In Nottingham, significant strides are being made in understanding and improving the experience of children and young people with mental health conditions and their families under the leadership of a postdoctoral NIHR Clinical Lecturer and jointly appointed professor (Carter et al, 2019;Manning et al, 2018). Similarly, the care and experiences of adults and children with Chronic Lymphedema are being transformed under the leadership of an internationally renowned Clinical Professor and local PhD clinical academics and specialist teams (Quéré et al, 2019), with strategic ambitions to transform services at NUH and across the wider community of Nottinghamshire.…”
Section: Improving Patient Outcomesdeveloping Services and Interventionsmentioning
confidence: 99%
“…In Nottingham, significant strides are being made in understanding and improving the experience of children and young people with mental health conditions and their families under the leadership of a postdoctoral NIHR Clinical Lecturer and jointly appointed professor (Carter et al, 2019;Manning et al, 2018). Similarly, the care and experiences of adults and children with Chronic Lymphedema are being transformed under the leadership of an internationally renowned Clinical Professor and local PhD clinical academics and specialist teams (Quéré et al, 2019), with strategic ambitions to transform services at NUH and across the wider community of Nottinghamshire.…”
Section: Improving Patient Outcomesdeveloping Services and Interventionsmentioning
confidence: 99%
“…Obesity is not necessarily unique to this cohort, as it has estimated that 63.4 per cent of Australian adults are considered overweight [58]. There is growing evidence that being obese is a significant risk factor for CO [15, 59, 60] however it was infrequently highlighted by the study cohort.…”
Section: Discussionmentioning
confidence: 95%
“…Accordingly, a previous study reported a CO prevalence rate of 28.5 percent amongst hospital inpatients [11]. According to the most recent and largest epidemiology international study on CO, the ‘Lymphedema IMpact and PRevalence INTernational’ (LIMPRINT), that involved collaboration across nine countries and 13,141 participants, there was a higher prevalence rate of 38% (723 patients) amongst acute hospital inpatients [14, 15]. Significant risk factors associated with CO were reported to be advancing age, obesity, immobility and comorbidities including diabetes mellitus [15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations